Manajemen Program Berita Televisi â€œKanal 22â€ Di Stasiun Tvri Yogyakarta (Perubahan Pola Siaran 6 Jam Ke 4 Jam) - DA, NRA. Candra; Rochmadi, Andis Dwi (Capture : Jurnal Seni Media Rekam, 2014)
The study aimed to determine changes in the management of the broadcastpattern of six hours to four hours through the television news program â€œChannel 22â€in TVRI Yogyakarta. This study used a descriptive research method with the review ofqualitative approaches. Location of this research is in TVRI Yogyakarta, source of dataincludes primary data and secondary data. The primary data obtained directly throughfield observations, interviews with informants, and literature. Techniques validity of thedata used is triangulation (triangulation, triangulation techniques, and triangulation oftime). Process analysis was performed using an interactive analysis model, then, thepresent data using sentences and utterances of researchers logically and systematically.The results of this study indicate that the broadcast pattern of six hours to four hours(in the news â€œChannel 22â€) on TVRI Yogyakarta in 2013, a change that does appear inthe English language news material planning more emphasis on new material, so thatthe need for coverage in field, and not just repeat the news items that have been aired.In the new program (news â€œChannel 22â€) contained deletion segments that existed inprevious news program (â€œYogya Wartaâ€ and â€œBeritaJogyaâ€). In terms of content, thecontent of broadcast news and information not meet the actual nature of the news andup to date. In addition, there is no certainty that the target audience looks at theprovision of the logo is still ambiguous.Keywords: management, television, broadcast, channel 22, and TVRI Yogyakarta